2021
DOI: 10.33559/esr.v2i3.623
|View full text |Cite
|
Sign up to set email alerts
|

Uji Efektivitas Ekstrak Buah Anggur Hijau (Vitis Vinivera L) Terhadap Daya Hambat Laju Pertumbuhan Bakteri Streptococcus Mutans Dan Lactobacillus Acidophilus

Abstract: Streptococcus mutans dan Lactobacilli adalah penghasil asam dari karbohidrat yang dapat diragikan dan menciptakan risiko untuk gigi berlubang, anggur hijau (Vitis vinifera L) merupakan salah satu jenis buah yang mengandung fitokimia golongan polifenol yang berfungsi sebagai penghambat glukosilasi pada proses pembentukan plak sehingga digunakan sebagai alternatif antibakteri dalam pencegahan karies. Tujuan penelitian ini adalah untuk mengetahui efektifitas antibakteri anggur hijau terhadap Streptococcus mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…10 Penggunaan chlorhexidine jangka panjang memberikan efek samping sehingga diperlukan bahan alternatif yang lebih aman digunakan. 11,12 Buah delima merah (Punica granatum L.) merupakan salah satu bahan yang banyak digunakan sebagai obat tradisional , karena buah ini memiliki potensi antibakteri kuat. 13,14 Delima merupakan tanaman buah-buahan berasal dari negara Iran, dan banyak ditemukan tumbuh di daerah Cina Selatan dan Asia Tenggara termasuk Indonesia.…”
Section: Pendahuluanunclassified
“…10 Penggunaan chlorhexidine jangka panjang memberikan efek samping sehingga diperlukan bahan alternatif yang lebih aman digunakan. 11,12 Buah delima merah (Punica granatum L.) merupakan salah satu bahan yang banyak digunakan sebagai obat tradisional , karena buah ini memiliki potensi antibakteri kuat. 13,14 Delima merupakan tanaman buah-buahan berasal dari negara Iran, dan banyak ditemukan tumbuh di daerah Cina Selatan dan Asia Tenggara termasuk Indonesia.…”
Section: Pendahuluanunclassified
“…Phytochemical compounds in polyphenol also include proanthocyanidins, which are used in the dentin remineralization process and provide protection for collagen matrix. 6 Grapes were chosen based on the research conducted by Rachmawati et al 13 and Busman et al, 25 which proved that grapes can be antibacterial, especially against cariogenic bacteria such as Streptococcus mutans. Another fundamental ingredient is fluoride that can prevent demineralization, enhance remineralization and act as a bacterial agent.…”
Section: Introductionmentioning
confidence: 99%
“…These three essential ingredients can be potentially put together to invent a cream to prompt tooth remineralization and treat white spot lesions. 25,26 Candidates for the remineralization cream should accomplish good quality and be applicable; hence, they must run several tests to achieve the standards so that it can be used in society. The remineralization cream underwent several tests such as a pH test, where a result of 4.5-10.5 was the standard for a favorable and intact product and a viscosity test, where the result would determine how substantial and adequate important ingredients of the material could diffuse into the microporosity of the enamel, which had an impact of triggering remineralization with the ideal number between 20 and 500 dPa.s.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is crucial for orthodontists to prevent microorganisms from adhering to orthodontic appliances. 6 The usage of aesthetic brackets and archwires is growing in popularity as orthodontic treatment for adult patients is becoming more common. However, several studies have demonstrated that the use of orthodontic appliances brings about changes in the oral environment, including increased levels of Lactobacillus acidophilus in the saliva and biofilm.…”
Section: Introductionmentioning
confidence: 99%